Will it survive? challenges faced by Islamic banking and finance in today’s world - Jan, Muhammad Tahir (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM)., 2018)
Despite the significant accomplishments made by Islamic banks over the past decades, there are still some notable issues from a marketing of financial services point of view that require attention in order to strengthen their market position relative to their conventional banking counterparts. Based on a review of extant literature this paper submits that with due recognition of the Islamic banks’ peculiar practical and regulatory milieu, financial products development in its entire ramifications is a sine qua non for continuous but sustainable growth of the Islamic banks. This should be complemented by developing a robust legal structure that enhances operational efficiency without infringing on growth potentials.